Longitudinal Force Simulation for Heavy Haul Train Based on Cycle Variable Method - ZHAO Xindi; GUO Qiyi; LYU Jie; WANG Mengchao (机车电传动)
The operation of heavy haul train was based on dynamics modeling and traction simulation calculation. According to the limitation of traditional research, a mathematical simulation model of longitudinal force of heavy haul train based on cycle variable was established. The model had been verified by the simulation though a train marshalling of 2Loco+14Car, 9 units. The results of the coupler force curves and its distribution along the whole train in different running conditions were provided, which verified that a train marshalling of 2Loco+14Car, 9 units could meet the safe operation requirement